Analysis of a maritime versus a landlocked tourism dependent economy: Croatia and the Czech Republic - Filip Kokotovic (UTMS Journal of Economics, 2017)
The relevance of tourism revenue to their respected GDP is comparable in Croatia and the Czech Republic. Aside from having comparable levels of tourism dependency in respect to the percentage of tourism revenue in GDP, there are very few significant structural similarities between the economies of Croatia and that of the Czech Republic. The simple geographic difference of a land-locked versus a maritime economy does not seem to be the most dominant feature in differentiating these two economies. Rather, through Impulse Response Functions (IRFs) and variance decompositions, this paper examines the relationship between the economic growth, public debt-to-GDP ratio, tourism revenue and the unemployment rate by implementing a Vector Autoregressive (VAR) framework. Through this framework, this paper detects structural differences between the economies of Croatia and the Czech Republic. Most notably, this paper concludes that tourism revenue is unable to combat the difficulties presented by macroeconomic imbalances in Croatia. It further concludes that Croatia should strive towards a more diversified economy and attempt to contain the difficulties it faces regarding its public debt and budget deficit.
Keywords: H63; Z32; 330; VAR; Impulse Response Functions (IRFs); macroeconomic imbalances; public debt-to-GDP ratio; sustainable growth